Stabilization of Voltage Parameters of Induction Generator Excited by a Voltage Inverter - Padalko D.A. (Problems of the Regional Energetics)
The article reveals the operational aspects of induction generator. Methods for stabilization of induction generator (IG) parameters under inverter excitation are investigated. The study was carried out using mathematical description and simulation modeling in MATLAB Simulink. The paper provides analysis of causes of generated voltage amplitude and frequency displacement when the loading condition and the rate vary. Due to the parametric resonance nature of IG self-excitation, the author introduces the expression that allows estimating the capacitor capacitance required to maintain the generation process, depending on the rotor speed of electric machine, load nature and rate. Based on the studies, it was proved that it is possible to stabilize the IG voltage parameters by maintaining the magnetizing circuit inductance Lm at the constant level., and realizing a control law close to U/f = const. The study proves that using the inverter together with the voltage regulator allows ensuring the quality of electricity corresponding to modern standards. The necessity of problem solving of the required quality of the voltage by the harmonic component for the exciter - inverter with PWM is shown. The prospects of the power generation system based on induction machine (IM) with a semiconductor frequency converter, which serves as an adjustable supplier of capacitive current for IM for autonomous objects, are substantiated. The use of semiconductor frequency converters makes it possible to provide high stability of the output voltage parameters and good speed of the mechatronic generation system with an asynchronous machine.